Influence of Bacteria on Compressive Strength and Durability of Concrete Made with Cement by Pass Dust - Nanda, Vasu (My University, 2015)
Rapid industrialization and urbanization increases the demand of building and construction material for infrastructure development. Generation of cement by-pass dust (CBPD) during cement clinker manufacturing has become one of the major environmental and economical issues. Globally, cement industries generate tons of cement by-pass dust every year as a measure to control product quality and to ensure uninterrupted operation of the plant. In order to reduce disposal costs utilization of CBPD as construction or land fill material has become an alternative to its disposal. Cement by-pass can be used as partial replacement in concrete. This study presents the utilization of cement by-pass dust in control and bacterial concrete, cement by-pass dust as partial replacement of Portland cement (0, 10, 20 and 30%) on the normal consistency, setting times and hydration process of blended cement pastes, and on compressive strength at 28 and 56 days of curing of control and bacterial concrete was investigated. Several properties such as compressive strength, water absorption and porosity, RCPT and sorptivity of control and bacterial concrete was also studied at the age of 28 and 56 days. Calcite producing bacteria AKKR5 was mixed in water during concrete mixing. SEM and XRD analysis confirmed formation of calcite. Control and bacterial Concrete with 0% CBPD achieved best results for compressive strength of 32.89 N/mm2 and 34.66 N/mm2, respectively as the percentage of CBPD increased the compressive strength decreased. Water absorption was significantly reduced in bacterial concrete. The chloride permeability of concrete specimens containing control and bacterial concrete CBPD showed “moderate” to “low” permeability with increasing curing period from 28 to 56 days except 30% CBPD concrete which falls in “High” chloride permeability range. Scanning electron microscopy (SEM) results exhibits formation of non-expansive ettringite in pores and increased calcium silicate hydrate (CSH) which dense the mortar and concrete structure, and thus, increases the compressive strength in bacterial concrete CBPD concrete.X-ray diffraction(XRD) analysis confirmed the formation of CSH and non- expansive ettringite within the matrix of bacterial concrete specimens responsible for improvement in the strength of the material. It was also found that CBPD alone is not cementitious in nature and replacing it with cement will reduce cement content. But upto 10 % CBPD replacement there was 14 % decrease (27.23 N/mm2) in strength which is acceptable in accordance to design target strength (26 N/mm2) obtained for M20 grade concrete.
M.E. (Structural Engineering)
Keywords: Bacteria; Concrete; Cement By-Pass Dust; Strength; Durability; structural engineering; civil engineering; CED